2015
DOI: 10.1016/j.jssc.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and second harmonic generation in a novel diamond-like semiconductor: Li2MnSnS4

Abstract: Polymorphism and Second harmonic generation in a novel diamond-like semiconductor: Li 2 MnSnS 4 , Journal of Solid State Chemistry, http://dx. Abstract:High-temperature, solid-state synthesis in the Li2MnSnS4 system led to the discovery of two new polymorphic compounds that were analyzed using single crystal X-ray diffraction. The α-polymorph crystallizes in Pna21 with the lithium cobalt (II) silicate, Li2CoSiO4, structure type, where Z=4, R1=0.0349 and wR2=0.0514 for all data. The β-polymorph possesses the wu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 66 publications
(95 reference statements)
1
26
0
Order By: Relevance
“…Initially, we attempted to prepare Li 2 HgGeS 4 with the ratio of Li:HgS:Ge:S = 2:1:1:3 at the reaction temperature of 700 • C. After the single crystal X-ray diffraction measurement, Li 4 HgGe 2 S 7 (main product, yellow) [79] and Li 2 HgGeS 4 (a small amount, reddish) were interestingly obtained. In addition, we had further adjusted the ratio of reactants and interestingly found that the pure-phase of Li 2 HgGeS 4 could be obtained while the ratio of Li:HgS is greater than 2:1.…”
Section: Hggesmentioning
confidence: 99%
“…Initially, we attempted to prepare Li 2 HgGeS 4 with the ratio of Li:HgS:Ge:S = 2:1:1:3 at the reaction temperature of 700 • C. After the single crystal X-ray diffraction measurement, Li 4 HgGe 2 S 7 (main product, yellow) [79] and Li 2 HgGeS 4 (a small amount, reddish) were interestingly obtained. In addition, we had further adjusted the ratio of reactants and interestingly found that the pure-phase of Li 2 HgGeS 4 could be obtained while the ratio of Li:HgS is greater than 2:1.…”
Section: Hggesmentioning
confidence: 99%
“…Compared with other metal chalcogenides classified as DLSs in the I 2 -II-IV-VI 4 systems, Li 2 MnSnSe 4 has as imilar unit cell to the Li-containing metal selenides that crystallize in the orthorhombic system, such as Li 2 CdMSe 4 (M = Ge, Sn), [13] however, the cell volume of Li 2 MnSnSe 4 (405.19 3 )i sc learly larger than these Li-containing metal sulfides due to the introduction of the larger Se atom, like Li 2 FeSnS 4 (341.7 3 ), [18] Li 2 MnSnS 4 (351.7 3 ), [19] and Li 2 MnGeS 4 (330.8 3 ). [20]…”
Section: Crystal Structurementioning
confidence: 99%
“…Nevertheless, the more diffuse natureo ft he electron orbitals of Sn and/or Se atoms make the SnSe 4 tetrahedra more susceptible to polarization, leadingt ot he stronger NLO response of Li 2 MnSnSe 4 than Li 2 MnMS 4 (M = Ge, Sn). [19,20]…”
Section: Nlo Propertymentioning
confidence: 99%
“…This value is slightly smaller than the optical bandgap of ca. 2.3 eV found in the analogous lithium compound Li 2 MnSnS 4 …”
Section: Resultsmentioning
confidence: 84%
“…This could indicate a phase‐transition to another polymorph with higher symmetry (e.g. orthorhombic symmetry), as observed for example in the parent compound Li 2 MnSnS 4 . However, as the diffraction pattern only slightly changes compared to the ambient temperature modification, a Rietveld refinement of this phase could not confirm this higher symmetry.…”
Section: Resultsmentioning
confidence: 93%